Przesłanki wykorzystania rachunku kosztów działań w instytutach naukowo-badawczych - Nóżka, Agnieszka (Premises of implementing activity based costing in research and development entites, 2006)
Activity Based Costing is a new cost accounting concept popular among academics and managers. It presents a modem cost analysis and uses the process based concept of entity (unit) performance measurement. The effective management of R&D entities in new operational circumstances requires modem and efficient information systems to which cost accounting system belongs. Cost accounting plays a major role in a corporate information system due to its significance in relation to decision taking parameters. The aim of the article is to show how to measure the suitability of ABC methodology in R&D entites to meet the above requirements. The basic rationales to introduce Activity Based Costing and Activity Based Management are increasing indirect costs, varying activities performed and potential advantages to these institutes.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1136, s. 338-344